Liver X receptor agonist inhibits HIV-1 replication and prevents HIV-induced reduction of plasma HDL in humanized mouse model of HIV infection - Dubrovsky, Larisa; Duyne, Rachel Van; Senina, Svetlana; Guendel, Irene; Pushkarsky, Tatiana; Sviridov, Dmitri; Kashanchi, Fatah; Bukrinsky, Michael (Biochemical and biophysical research communications, 2012)
► The first demonstration that the effect of HIV infection on HDL can be reproduced in a humanized mouse model of HIV infection. ► Demonstration of anti-HIV activity of LXR agonist in an NSG mouse model of HIV infection. ► Demonstration of protective effect of LXR agonist against HIV-induced reduction of HDL levels in blood. ► Supportive evidence for the indirect mechanism of HIV-induced HDL impairment through the release of a soluble factor. HIV-infected subjects are at high risk of developing atherosclerosis, in part due to virus-induced impairment of HDL metabolism. Here, using as a model of HIV infection the NOD.Cg-PrkdcscidIL2rgtm1Wjl/SzJ (NSG) mice humanized by human stem cell transplantation, we demonstrate that LXR agonist TO901317 potently reduces viral replication and prevents HIV-induced reduction of plasma HDL. These results establish that humanized mice can be used to investigate the mechanisms of HIV-induced impairment of HDL formation, a major feature of dyslipidemia associated with HIV-1 infection, and show potential benefits of developing LXR agonists for treatment of HIV-associated cardio-vascular disease.